The rules of the academic game: reviewing the history of Australian higher education - Phillips, Matthew James (Frontiers in Education, 2024)
The Australian higher education system has its origins in the 'Oxbridge' model, and while traces of its Eurocentric heritage persist, the system has evolved through a blend of continuity and change. To grasp the trajectory of Australian higher education, it is essential to delve into its historical development and the pivotal events that have shaped its current form. This article explores significant milestones in the establishment of Australian higher education, all within the backdrop of Australia's history as a colonised nation transitioning to Federation in the 20 th century. Embedded within this commentary is a recognition of the intricate challenges faced by academics within the realm of higher education. Historically, academia has remained an exclusive and elitist sphere, marked by imperial and patriarchal norms that have favoured white, heterosexual men. These norms have perpetuated the perception of their superiority, consequently influencing how minority groups have navigated academia, both as students and academics. The institutionalisation of political, economic, and symbolic ideologies has further exacerbated the obstacles encountered within academia. Therefore, it becomes paramount to consider the impact of the higher education system's operations on academics and how it has perpetuated the influence of colonialism and imperialism on the shaping of scientific knowledge and practices throughout history.